Global Jihadist Terrorism : Terrorist Groups, Zones of Armed Conflict and National Counter-Terrorism Strategies - Burke, Paul; Elnakhala, Doaa'; Miller, Seumas; Burke, Paul; Elnakhala, Doaa'; Miller, Seumas (Cheltenham, Gloucestershire, UK and Northampton MA, USA Edward Elgar Publishing)
This insightful book provides a unified repository of information on jihadist terrorism. Offering an integrated treatment of terrorist groups, zones of armed conflict and counter-terrorism responses from liberal democratic states, it presents fresh empirical perspectives on the origins and progression of conflict, and contemporary global measures to combat terrorist activity.
English
Keywords: JPWL; JPWL2; LNFV; JPS; International terrorism; Counter-terrorism responses; Terrorist attacks; Terrorism legislation; Intelligence and Security Agencies; Jihadist